2020
DOI: 10.3390/molecules25225416
|View full text |Cite
|
Sign up to set email alerts
|

Thuja occidentalis L. (Cupressaceae): Ethnobotany, Phytochemistry and Biological Activity

Abstract: Thuja occidentalis L. (Cupressaceae) has its origins in Eastern North America and is cultivated in Europe and Brazil as an ornamental tree, being known as the “tree of life” or “white cedar”. In traditional medicine, it is commonly used to treat liver diseases, bullous bronchitis, psoriasis, enuresis, amenorrhea, cystitis, uterine carcinomas, diarrhea, and rheumatism. The chemical constituents of T. occidentalis have been of research interest for decades, due to their contents of essential oil, coumarins, flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
(122 reference statements)
0
29
0
1
Order By: Relevance
“…Cell death after PDT is mediated predominantly through apoptosis which is associated with irreversible cell death (Villacorta et al, 2017). According to phytochemical studies, TO based preparations contain various active constituents including essentials oils, coumarins, flavonoids, tannins and proanthocyanidines (Caruntu et al, 2020). In a PDT setting, coumarins and its derivatives play an active role in research as a naturally occurring organic PS due its strong photophysical and photochemical properties (Köksoy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell death after PDT is mediated predominantly through apoptosis which is associated with irreversible cell death (Villacorta et al, 2017). According to phytochemical studies, TO based preparations contain various active constituents including essentials oils, coumarins, flavonoids, tannins and proanthocyanidines (Caruntu et al, 2020). In a PDT setting, coumarins and its derivatives play an active role in research as a naturally occurring organic PS due its strong photophysical and photochemical properties (Köksoy et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Coumarin derivatives were selected as the chromophore in the complex due to its photophysiochemical abilities (Gangopadhyay et al, 2015). In TO, coumarins are present in the form of p-coumaric acid (PCA), and umbelliferone (7-hydroxycoumarin) (Caruntu et al, 2020). PCA is a phenolic compound with antioxidant, anticancer and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Агропрепарат малотоксичен в отношении человека и животных, экологически нейтрален, не токсичен для растений. Действие препарата заключается в стимуляции корнеобразования, усилении хлорофиллогенеза, повышении устойчивости к бактериальным, вирусным и грибковым патогенам [8].…”
Section: ***** известия ***** н и ж н е в о лж с ког о а г р оу н и в...unclassified
“…Biota orientalis (also called Thuja orientalis or oriental arborvitae) is a slow growing coniferous tree that is native to China and Iran. Extracts from the plant are commonly used in Chinese herbalism (Caruntu et al, 2020). Preclinical in vitro and in vivo studies have demonstrated that extracts of Biota orientalis have antioxidant (Alamdari et al, 2017), and antiin ammatory (Jin et al, 2012;Kim et al, 2011Kim et al, , 2013Lee et al, 2010;Shin et al, 2015) activities.…”
Section: Introductionmentioning
confidence: 99%